Public participation in Integrated Water - Sansom-Sherwill, Tamsyn Anita. (My University, 2006)
South Africa’s new water policy and law have introduced the requirement for public participation in all aspects of resource management and decision-making. This policy change is in recognition of the potential benefits of participation in generating more informed, acceptable, equitable and sustainable management of the nation’s water resources. However the new water law does not prescribe the form this participation should take, or offer criteria for evaluating the success of participatory processes. The term ‘public participation’, in its contemporary usage worldwide, is poorly or broadly defined and may thus encompass a range of processes, which differ in the roles and influence afforded to their stakeholder participants, and in their ability to deliver desired outcomes and benefits to government or the public. This study aimed to investigate the influence of this procedural variation on public and stakeholder participation in the implementation of the National Water Act (Act no. 36 of 1998) in South Africa, and thereby recommend a preferred approach to conducting and facilitating these processes in the future. Use was made of a qualitative and primarily inductive research approach. This was designed to gather perspectives of the various role-players (stakeholders, specialists and government) for a desired process and outcome of participation, and to link process and outcome by means of two case studies of the current implementation of participatory processes for water resource management decision-making. Both case studies illustrated the over-riding negative influence of a product-oriented and ‘specialist-centred’ approach to participation, focused on the development of specific statutory products or decisions required by the National Water Act. This approach in turn is being driven by the current fragmentation of participation around these different products and stages of the overall resource management process. A recommended alternative is a more process-oriented, ‘stakeholder-centred’ approach to participatory events, within an integrative, ongoing participatory process. This must be based on mutual learning by all role-players, and an emphasis on inter-sectoral interaction and relationships. A key constraint identified to the achievement of more integrative participatory processes that offer influence to, and generate ownership by, stakeholder participants, is the lack of clarity within government and the South African water sector as to the intent of participation within the new water policy, and thus the process by which this participation should take place. In particular, the role of stakeholders, and how much influence or power they should be afforded in decision-making processes, is subject to individual interpretation. The recommendation from this research is that, given the ideals of equity, sustainability and citizen empowerment aspired to by the Constitution and the new water policy, government should strive to fully engage stakeholders in processes that both offer influence and inspire action. Ideally, linkages should be created to extend this influence to the broader political process.
Fsculty of Science School of Animal,Plant And Enviromental Sciences Msc 9201098j tsherwill@yahoo.com
Keywords: National Water Act; Participatory Natural Resource; Management; Deliberative democracy; Consensous decision making